Predicting Suicide Intent: The Roles of Experiencing or Committing Violent Acts. Issue 3 (29th September 2015) - Jordan, Joshua T.; Samuelson, Kristin W.
Abstract : According to the interpersonal theory of suicide (Joiner, 2005), repeated exposure to painful or provocative experiences is associated with lethal or nearly lethal suicide attempts. However, suicide research often focuses on suicide ideation or attempts, rather than intent. Using data from the Collaborative Psychiatric Epidemiological Surveys, we examined traumatic experiences, with a focus on repeated exposure to traumas, in individuals who described their suicide attempts as a strong intent to die versus a cry for help. Only repeated acts of committing violence were associated with high suicide intent, suggesting that individuals who engage in violence are at heightened risk for suicide.